2012
DOI: 10.1016/j.cell.2012.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Partial Agonism Drives Warburg-like Metabolism in Muscle and Brown Fat

Abstract: Diabetes, obesity, and cancer affect upward of 15% of the world's population. Interestingly, all three diseases juxtapose dysregulated intracellular signaling with altered metabolic state. Exactly which genetic factors define stable metabolic set points in vivo remains poorly understood. Here, we show that hedgehog signaling rewires cellular metabolism. We identify a cilium-dependent Smo-Ca(2+)-Ampk axis that triggers rapid Warburg-like metabolic reprogramming within minutes of activation and is required for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
254
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(263 citation statements)
references
References 64 publications
8
254
1
Order By: Relevance
“…Previous reports have suggested a role for HH-regulated Ca 2+ signaling during development (34) and in metabolic regulation (35). We show that HH signaling controls Ca 2+ dynamics to regulate ciliary cyclases and downstream signaling through cAMP to PKA and Gli proteins (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Previous reports have suggested a role for HH-regulated Ca 2+ signaling during development (34) and in metabolic regulation (35). We show that HH signaling controls Ca 2+ dynamics to regulate ciliary cyclases and downstream signaling through cAMP to PKA and Gli proteins (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Smoothened Agonist Promotes Satellite Proliferation through Activating AMPK-It has been recently reported that noncanonical Sonic Hedgehog (Shh) signaling promotes a Warburglike glycolysis in differentiated C2C12 myotubes (22). Therefore, we questioned whether this pathway is also present in undifferentiated myoblasts and satellite cells and whether AMPK␣1 has a mediatory role in eliciting Warburg-like glycolysis.…”
Section: Expression Of Ampk␣1 and Ampk␣2 During Skeletal Musclementioning
confidence: 97%
“…We first tested the effect of Smoothened (Smo) agonist (SAG), an activator of Shh pathway, on AMPK activity in C2C12 myoblasts and WT satellite cells. C2C12 myoblasts and WT satellite cells were treated with 200 nM SAG for only 10 min to avoid the activation of canonical Shh signaling (22,29). In both C2C12 cells and WT satellite cells, 10 min of SAG treatment activated AMPK (Fig.…”
Section: Expression Of Ampk␣1 and Ampk␣2 During Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of Gli activity may be necessary for engaging Shh in distinct signaling pathways and functions of the maturing and adult tissues. Noncanonical Shh signaling (47,48) is implicated in regulation of muscle and brown-fat metabolism (49) and, in the spinal cord, participates in neurotransmitter specification and axon guidance (28,50). Interestingly, in the adult ventrolateral nucleus of the tractus solitarius, Shh acutely modulates neuronal excitability (51).…”
Section: Discussionmentioning
confidence: 99%